Improved RTAB-Map Algorithm Based on Visible Light Positioning - Po-Hao Hunag; Si-Chuan Liu; Cheng-Hsiung Yang (IEEE Access)
Visible Light Positioning (VLP) is an emerging technology that enables highly accurate indoor localization, especially in areas where GPS is not effective, such as inside buildings. VLP makes use of existing lighting systems but typically requires a high density of Light Emitting Diodes (LEDs) and a clear line-of-sight (LOS) between the light sources and the receivers. It is also crucial to recognize that sensors can have limitations, and their readings may not always be precise. This research presents an improved RTAB-Map algorithm based on visible light positioning. By using a custom modulator, we send signals to the LEDs to create a striped pattern. A rolling shutter camera captures these LED signals and uses template matching techniques to accurately locate the region of interest (ROI). Within this ROI, we identify the LED contours and extract the pixels from the central row into a one-dimensional array for decoding. The decoded information is then compared to a pre-existing database. Finally, we apply the solvePnP algorithm to determine the three-dimensional position and orientation, which is integrated with Kalman Filters to combine the data into the RTAB-Map algorithm for mapping purposes. This multi-sensor localization system shows strong and accurate capabilities for robot localization and navigation, even in scenarios with limited LEDs or power outages. Experimental results reveal that the proposed method achieves an average accuracy of 2.5 cm and an average positioning delay of about 5.3 microseconds.